Pengaruh Pelatihan Kerja Dan Kompensasi Terhadap Kinerja Karyawan Dengan Motivasi Ekstrinsik Sebagai Variabel Intervening (Studi Pada PT. GPS Cabang Tangerang) - sugeng budi satriyo (Sains Manajemen : Jurnal Manajemen UNSERA, 2021)
ABSTRACT Job training and compensation are closely related to the ability to work and encourage employee motivation and will directly improve the performance they have. This research was conducted at PT. GPS Tangerang Banten Branch. This study aims to determine the effect of job training and compensation mediated by intrinsic motivation on employee performance. The number of samples determined was 91 respondents using the census method. As an independent variable, namely job training and compensation, and the intervening variable is intrinsic motivation, while the dependent variable is employee performance. The analytical method used in this research is Partial Least Squares-Structural Equetion Modeling (PLS-SEM) with Smart PLS 3.0. includes structural model test or inner model, hypothesis testing, outer model measurement model and sobel test. From the analysis, it can be seen that job training variables do not directly affect employee performance variables. This can be seen from the t-statistic value which is smaller than 1.960, which is 0.806, or indirectly through intrinsic motivation. This can be seen from the sobel test that the t value is lower than 1,960, which is 0.020. And the test results on Inderect Effects show that the indirect relationship of the Job Training (JT) variable with Employee Performance (EP) through Intrinsic Motivation (IM) shows a path coefficient value of 0.001 with a t value of 0.030. This value is smaller than t table (1,960). As for the compensation variable has a positive and significant effect on performance and the intrinsic motivation variable can mediate compensation on employee performance. Furthermore, the results of the R-square value show that the Job Training (JT) and Compensation (Co) variables can explain the Intrinsic Motivation (IM) variable by 35.3%, the remaining 66.7% is explained by other variables not examined in this study. Furthermore, the Job Training (JT) variable and the Compensation (Co) variable can also explain the Employee Performance (EP) variable of 56.5%, the remaining 43.5% is explained by other variables not examined in this study. Keywords: Job Training, Compensation, Intrinsic Motivation and Employee Performance